Geothermal Prospect Selection Using Analytical Hierarchy Process (AHP): A Case Study in Sulawesi Island, Indonesia - Suryantini, Suryantini; Wibowo, H. (Geological Agency, 2010)
DOI:Â 10.17014/ijog.v5i4.107Analytical Hierarchy Process (AHP) is a Multi Criterion Decision Making (MCDM) Technique. It can handle any complex, multicriterion, and multiperson problems. In AHP, the problems are decomposed into a hierarchically structure and are given the weights according to its importance. Thus, the strength with which one alternative dominates another with respect to a given criterion can be identified. The output is a priority ranking indicating the overall preference for each decision alternative. This paper describes the application of AHP to select a geothermal prospect in Sulawesi Island to be developed in the near future. The alternatives consist of three geothermal prospects. i.e., Suwawa, Pulu, and Marana. Three major criteria are used and applied into those three prospects: Geoscience, Infrastructure, and Social-culture aspects. Under each of these major criteria, there are several subcriteria. Geoscience criterion which consists of Resources, Geothermal System, and Geological Risk Subcriteria is given the highest weight with the assumption that if resources are large and can be developed commercially, then there is no reason not to be exploited; the technology and other infrastructure aspects are no longer an obstacle. The result shows that Suwawa Prospect is the best option to be developed in the near future. The second option or rank is Marana Prospect, and the third is Pulu Prospect. This result is in agreement with the future plan of the development of Sulawesi Island. If the regulation and plan of development were suddenly changed, the goal of this AHP might not be appropriate anymore, and the second or third option might replace the first rank. The benefits of using AHP are (1) the facts and reasons behind the decision are well documented, (2) able to handle quantitative and qualitative inputs, (3) able to accommodate environmental, social and other influences, and (4) able to handle subjective judgments of individuals. Lessons learned from AHP application for geothermal prospect selection could be extended into multi criterion decision making at a group level.